Risk factors for food insecurity and association with prenatal care utilization among women who took opioids during pregnancy and unexposed controls - Lindsay M. Parlberg; Jamie E. Newman; Stephanie L. Merhar; Brenda Poindexter; Sara B. DeMauro; Scott A. Lorch; Myriam Peralta-Carcelen; Deanne E. Wilson-Costello; Namasivayam Ambalavanan; Catherine Limperopoulos; Nicole Mack; Jonathan M. Davis; et al. (BMC Pregnancy and Childbirth)
Abstract Background Food insecurity during pregnancy is associated with poorer outcomes for both mothers and their newborns. Given the ongoing opioid crisis in the United States, mothers who take opioids during pregnancy may be at particular risk of experiencing food insecurity. Methods This research utilized data from 254 biological mothers of infants in the Advancing Clinical Trials in Neonatal Opioid Withdrawal Syndrome (ACT NOW) Outcomes of Babies with Opioid Exposure (OBOE) Study. We examined factors associated with food insecurity among mothers of infants with antenatal opioid exposure and their unexposed (control) counterparts. Chi-square tests and logistic regression were used to compare food insecurity by sociodemographic characteristics, opioid use, prior traumatic experiences, and housing instability. Similar analyses were conducted to examine the relationship between food insecurity during pregnancy and receipt of adequate prenatal care. Results Overall, 58 (23%) of the mothers screened positive for food insecurity. Prevalence of food insecurity was higher among mothers who took opioids during pregnancy compared to controls (28% vs. 14%; p = 0.007). However, the difference between the two groups was no longer significant after accounting for demographics, housing instability, and prior trauma (AOR (95% CI) = 1.85 (0.82, 4.20), p = 0.140). Mothers with food insecurity during pregnancy were less likely to have received adequate prenatal care (78% vs. 90%), after controlling for other factors (AOR (95% CI) = 0.39 (0.16, 1.00), p = 0.049). Conclusions Food insecurity frequently co-occurred with housing instability and prior trauma among mothers of infants with antenatal opioid exposure, for which limited data are available. Although those with food insecurity are at increased risk for poor pregnancy outcomes, they were less likely to have received adequate prenatal care despite high levels of public insurance coverage, suggesting alternative approaches are needed to address barriers to healthcare among this population. Wrap-around care models are recommended to provide multifaceted and continuous support during the perinatal period. Care models should provide for staff training in trauma-informed care and include resources to address housing and food concerns. Trial registration The Outcomes of Babies with Opioid Exposure (OBOE) Study is registered at Clinical Trials.gov (NCT04149509) (04/11/2019).